Sosialisasi Pembelajaran Tatap Muka Terbatas Pada Anak Usia Sekolah Dasar Di Kelurahan Srengseng Sawah Jakarta Selatan - Syahadah Albaqiyatul Karimah; Widya Rahmawati Al-Nur; Nurul Fauziyyah; Moh. Faiz Maulana (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2023)
This community service aims to equip elementary school-aged children dealing with the limited Face-to-Face Learning (FFL) of the covid-19 pandemic and provide knowledge related to clean and healthy living behavior. This activity used a demonstration method in which the facilitator team provided instructions and practices to participants maintaining personal hygiene in facing limited Face-to-Face Learning (FFL). The result of this community service is that participants are able to understand the things which must be prepared in facing limited face-to-face learning in each school specifically maintaining clean and healthy living behavior. Keywords: Face-to-Face Learning, School-aged Children, Clean and Healthy Living Behavior